Compensation profiles among private sector employees in Sweden: Differences in work-related and health-related outcomes - Nordgren Selar, Alexander; Gagné, Marylène; Hellgren, Johnny; Falkenberg, Helena; Sverke, Magnus (Frontiers in Psychology, 2023)
How experiences and perceptions of pay and pay setting relate to employees’ job performance, willingness to remain in the organization, and health has been the subject of much debate. Previous research has typically used a variable-centered approach to investigate associations between different pay-related factors and such outcomes. In contrast, we used latent profile analysis to explore combinations of compensation characteristics (pay level, perceived horizontal pay dispersion, and procedural quality, i.e., transactional leadership and procedural pay-setting justice), combining relevant theories on the subject. Based on a nationally representative sample of private sector employees in Sweden (N=1146), our study identified six compensation profiles. Our key findings show, first, that higher levels of pay were generally associated with better performance, lower turnover intention, better self-rated health, and lower work-related exhaustion, especially when combined with perceptions of high procedural quality. Second, in terms of perceived horizontal pay dispersion, the results indicate that pay compression may be associated with beneficial outcomes, particularly when combined with high procedural quality. Third, procedural quality was generally associated with favorable work-related and health-related outcomes, although such positive effects may be contingent upon pay level and perceived horizontal pay dispersion. In conclusion, while pay level, perceptions of horizontal pay dispersion, and procedural quality may all matter for employee outcomes, it is important to consider their combinations.